O perfil do professor de ensino supletivo: um estudo com enfoque nas suas representações contextuais reveladas pela categoria 'linguagem' - Machado, Terezinha Costa da Silva (1990)
This research about education and deals with 'Ensino Supletivo' - suplementary teaching. It was accomplished in order to profile the teacher of this area of education. Information was sought from books about this matter as well as people were intervewwed. While achieving the research work everything was done to find out in a dialectical methodology and within as social, political, economical, cultural context, the importance which comes from the work of those who practise suplementtary teaching. About this profile was inquired in public and governamental in the municipality from Rio de Janeiro. The research was divided in two main parts scools. 1st. Theorical inquiry - Here it was possible to find out that the suplementary teaching subject is not studied enough, may be, because it isn't important enough in educational politics at a national level. 2nd The inquiry about 'suplementary' at places were it's practised. At this the working conditions of the teaching professional wery investigated with his auxieties, his woes, his frustrations and specially his firm purpose of fíghting in order to be able to change and to free suplementary teaching from being called marginal and inefficient. In the final part conclusions are shown and here will have reached the ain of the research: to profile the suplementary teaching teacher. We don't think be at the end of this matter ar of exhausted it. On the contrary we had in mind a greater space, where everyone could in same way contribute to improve this part of education. Trine doesn't stop and this research is a part in this time space where it was carried out; therefore it may be made better at any moment.